2020
DOI: 10.3390/cancers12030711
|View full text |Cite
|
Sign up to set email alerts
|

Claudins: New Players in Human Fertility and Reproductive System Cancers

Abstract: Claudins are major integral proteins of tight junctions (TJs), the apical cell-cell adhesions that enable maintaining polarity of epithelial cells, their differentiation, and cell signaling. A number of studies have indicated that claudins might play a crucial role in both physiology and pathogenesis. Their tissue-specific expression was originally linked to the development of different types of cancer and triggered a hope to use them as diagnostic or prognostic markers. However, it seems that their expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 123 publications
1
8
0
Order By: Relevance
“…Claudins, together with occludins and junctional adhesion molecules, are three transmembrane components of tight junctions, playing the role of paracellular barrier and intracellular signaling, while regulating the proliferation, differentiation, and apoptosis of the epithelial cell ( Severson and Parkos, 2009 ; Liu F. et al, 2016 ; Osanai et al, 2017 ; Kage et al, 2019 ; Phattarataratip and Sappayatosok, 2020 ). It has been demonstrated that claudins are intimately involved in the majority of epithelial-derived cancers by altering their expression manners ( Baumholtz et al, 2017 ; Osanai et al, 2017 ; Singh et al, 2017 ; Tabaries and Siegel, 2017 ; Cherradi et al, 2019 ; Gowrikumar et al, 2019 ; Kage et al, 2019 ; Auguste et al, 2020 ; Koziel et al, 2020 ; Phattarataratip and Sappayatosok, 2020 ; Kolchakova et al, 2021 ). Recent studies have confirmed that CLDN6 could promote the cell migration and invasion of certain cancers, including breast cancer ( Liu Y. et al, 2016 ; Lu et al, 2017 ), gastric cancer ( Torres-Martinez et al, 2017 ; Yu et al, 2019 ), hepatocellular carcinoma ( Huang et al, 2020 ; Kong et al, 2020 ), and endometrial cancer ( Kojima et al, 2021 ), and can be vigorously stimulated in human-induced pluripotent stem cells developed from fibroblasts, thus might present to be a promising target candidate antibody for cancer therapy ( Türeci et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Claudins, together with occludins and junctional adhesion molecules, are three transmembrane components of tight junctions, playing the role of paracellular barrier and intracellular signaling, while regulating the proliferation, differentiation, and apoptosis of the epithelial cell ( Severson and Parkos, 2009 ; Liu F. et al, 2016 ; Osanai et al, 2017 ; Kage et al, 2019 ; Phattarataratip and Sappayatosok, 2020 ). It has been demonstrated that claudins are intimately involved in the majority of epithelial-derived cancers by altering their expression manners ( Baumholtz et al, 2017 ; Osanai et al, 2017 ; Singh et al, 2017 ; Tabaries and Siegel, 2017 ; Cherradi et al, 2019 ; Gowrikumar et al, 2019 ; Kage et al, 2019 ; Auguste et al, 2020 ; Koziel et al, 2020 ; Phattarataratip and Sappayatosok, 2020 ; Kolchakova et al, 2021 ). Recent studies have confirmed that CLDN6 could promote the cell migration and invasion of certain cancers, including breast cancer ( Liu Y. et al, 2016 ; Lu et al, 2017 ), gastric cancer ( Torres-Martinez et al, 2017 ; Yu et al, 2019 ), hepatocellular carcinoma ( Huang et al, 2020 ; Kong et al, 2020 ), and endometrial cancer ( Kojima et al, 2021 ), and can be vigorously stimulated in human-induced pluripotent stem cells developed from fibroblasts, thus might present to be a promising target candidate antibody for cancer therapy ( Türeci et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the occurrence of particular claudins is determined by tissue and may differ depending on the type of the organism (Table 1). Their expression and location may be modulated by many substances including hormones [2]. For example, the estrogenic-like mycotoxin-zearalenone stimulated inflammation, disrupted the intestinal microflora and decreased the expression of claudin-4 in piglet intestine [24].…”
Section: Claudins In Intestines-schedule and Function In Healthmentioning
confidence: 99%
“…The functioning of the intestinal barrier might be influenced by many factors including diet or lifestyle. At the molecular level, these factors may affect claudin expression and, by disturbing the connection and permeability of the epithelium, leading to many pathological conditions such as cancer development or its progression [2]. Claudins are a family of proteins that take part in the formation of tight junction connections between cells.…”
Section: Introductionmentioning
confidence: 99%
“…Tight junction proteins are major structural components that determine paracellular integrity of brain endothelium, which regulates endothelial cell permeability, and creates a barrier, through cell adhesion, that limits access to the cerebrospinal fluid environment. 42 , 43 , 44 Studies have found that an increase in blood–brain barrier permeability is accompanied by a decrease in the expression of tight junction proteins, 44 , 45 whereas Rho kinase (ROCK), which is activated by RhoA GTPases, can induce phosphorylation of tight junction proteins, leading to their disruption and promoting the migration of monocytes through the blood–brain barrier. 46 Tumor cells can interfere with the expression of tight junction proteins and extravasate and spread into the brain between disrupted tight junction proteins.…”
Section: Mechanisms Of Aerobic Exercise In Tumor Hypoxiamentioning
confidence: 99%
“…In addition, Rho is a redox sensitive small GTPase whose activation is associated with destabilization and increased permeability of the endothelial barrier during tumorigenesis. Tight junction proteins are major structural components that determine paracellular integrity of brain endothelium, which regulates endothelial cell permeability, and creates a barrier, through cell adhesion, that limits access to the cerebrospinal fluid environment 42‐44 . Studies have found that an increase in blood–brain barrier permeability is accompanied by a decrease in the expression of tight junction proteins, 44,45 whereas Rho kinase (ROCK), which is activated by RhoA GTPases, can induce phosphorylation of tight junction proteins, leading to their disruption and promoting the migration of monocytes through the blood–brain barrier 46 .…”
Section: Mechanisms Of Aerobic Exercise In Tumor Hypoxiamentioning
confidence: 99%